Organizational stressors and basic psychological needs: The mediating role of athletes' appraisal mechanisms - Bartholomew, K. J.; Arnold, R.; Hampson, R. J.; Fletcher, D. (Scandinavian Journal of Medicine & Science in Sports, 2017)
This paper reports the first study to quantitatively examine the relationships between the demands encountered by athletes that are associated with the organization within which they are operating, cognitive appraisals, and basic psychological need experiences. Three hundred and fifteen high-level British athletes completed a multi-section questionnaire which assessed each of the aforementioned constructs. A series of path analyses provided valuable insight into the way in which the three dimensions (i.e., frequency, intensity and duration) of five organizational stressor categories were evaluated by athletes and, in turn, how such threat or challenge appraisals predicted feelings of need satisfaction and need frustration. Moreover, cognitive stress appraisals were found to mediate the relationship between organizational stressors and psychological need experiences. The role of secondary control appraisals was also explored and found to mediate the relationship between primary cognitive appraisals and basic psychological need experiences. Study limitations, proposed future research directions, and the implications of the findings for applied practitioners are discussed.